2017
DOI: 10.18632/oncotarget.19318
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 and PD-L1 co-expression predicts favorable prognosis in gastric cancer

Abstract: While the prognosis of gastric cancer (GC) remains poor, PD-1 and PD-L1/L2 are promising prognostic biomarkers. We evaluated PD-1 and PD-L1/L2 expression in tumor cells (TCs) and tumor-infiltrating immune cells (TIICs). We determined the Helicobacter pylori (Hp) and Epstein-Barr virus (EBV) infection status in a GC cohort (n=340), then analyzed the relationship between the expression of PD-1, PD-L1/L2 and GC prognosis. We found that PD-1, PD-L1, and PD-L2 mRNA levels were up-regulated in GC tissues, and were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 54 publications
(58 reference statements)
4
63
0
Order By: Relevance
“…demonstrated PD-1 to be an independent prognostic factor for both OS and disease-free survival in patients with MSS tumours. 17 Moreover, PD-1 expression has been demonstrated to carry an independent favourable impact in gastric, 47 ovarian, 48 and head and neck cancer, 49 among others. Further studies are warranted to elucidate the prognostic impact of PD-1 expression in CRC, particularly regarding PTL.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated PD-1 to be an independent prognostic factor for both OS and disease-free survival in patients with MSS tumours. 17 Moreover, PD-1 expression has been demonstrated to carry an independent favourable impact in gastric, 47 ovarian, 48 and head and neck cancer, 49 among others. Further studies are warranted to elucidate the prognostic impact of PD-1 expression in CRC, particularly regarding PTL.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of multiple cancer types using immunohistochemical (IHC) analysis, PD-1 ligand 1 (PD-L1) protein expression on tumor cells and tumor-infiltrating immune cells have been reported to be associated with patient prognosis [6][7][8] and the response to PD-1/ PD-L1-targeted therapy [9,10]. Thus, PD-L1 protein expression is considered a potential biomarker of prognosis and therapeutic benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, PD-L1 protein expression is considered a potential biomarker of prognosis and therapeutic benefit. However, in GC patients, the prognostic significance of PD-L1 protein expression in tumor cells and immune cells is still controversial [6][7][8][11][12][13][14], as is that of PD-1 [8,15] and CD8 [12,14,16] protein levels, probably because of different antibody clones, cutoff values for positivity and technical methods [6]. On the other hand, although a few studies have evaluated the association between PD-L1 mRNA levels and prognosis in GC [17,18], data acquired by mRNA analysis are quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, many studies have demonstrated that PD‐1, PD‐L1, or PD‐L2 protein expression are associated with survival of the solid tumors . In our previous study, we also found that the co‐expression of PD‐1 and PD‐L1 was a favorable prognostic marker in regard to the mortality risk of GC patients . However, the assessment of PD‐L1 status in tumors by the immunohistochemical (IHC) method still needs standardization .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] In our previous study, we also found that the co-expression of PD-1 and PD-L1 was a favorable prognostic marker in regard to the mortality risk of GC patients. 10 However, the assessment of PD-L1 status in tumors by the immunohistochemical (IHC) method still needs standardization. 11,12 Therefore, more stable and consistent markers associated with the PD-1 and PD-L1 pathway need to be identified for the prognostic evaluation of cancer.…”
Section: Introductionmentioning
confidence: 99%